Vulnerabilidad en los establecimientos de salud de Tarapoto - Pinchi Silva, Juan Carlos (2008)
Carry out studies of vulnerability to the establishments of health aims to ensure the protection of the life, performance, and investment. As it is possible to determine in the three settlements of health, Hospital 11 - Tarapoto (MINSA), maternal child Center (ESSALUD) and Health Center April 9 (MINSA), there has been an evaluation prior to any natural disaster (earthquake), which caused that after the earthquake of the 2,005 newly become studies post earthquake to alleviate the damage. The scope of the assessment of vulnerability of settlements does not end by quantifying the degree of vulnerability and the need for intervention if not determine the type of proper rehabilitation to which shall be subject the structure and ending in the formulation of technical dossiers for easy and speedy execution. The Peru, is one of the countries with significant seismic activity in the world, is mainly related to the process of subduc...